Strategy of the School’s Principal in Improving Learning Management Excellence at SMA Negeri 1 Gunung Megang - Deriyusmita, Deriyusmita; Harapan, Edi; Rahman, Andi (Journal of Social Work and Science Education, 2023)
This study describes in depth the Principal’s Strategy in Improving Learning Management at SMA Negeri 1 Gunung Megang. This study uses a descriptive qualitative approach. Data collection was carried out using interview methods, observation methods, and documentation with research instruments in the form of observation guidelines and interview guidelines. Data analysis techniques include data reduction, data presentation, and conclusion drawing, research informants namely the principal, deputy principal, and teacher. The results of the study show that: (1) Implementation of Learning Management at Gunung Megang 1 Public High School includes all implementation and activities carried out in a transparent and open manner and then always coordinates with the school committee and involves both academic and non-academic (2) Supporting factors in the leadership of school principals in SMA is the support of all teachers and staff, (3) supervision carried out by the principal at SMA Negeri 1 Gunung Megang, Muara Enim Regency, always evaluates every activity.